3D printing of cell‐free implants: A promising avenue for cartilage regeneration and joint preservation - Liangbin Zhou; Shangsi Chen; Boguang Yang; Yiting Lei; Hegeng Li; Haoyue Luo; Xiaoshuai Wang; Qiongjiao Zeng; Jiahui Lai; Fei Jin; Rocky S. Tuan; Zhong Alan Li (Interdisciplinary Medicine, 2026)
Abstract Cartilage regeneration and joint preservation are confronted with tremendous challenges. Traditional cell‐based treatments, while effective in some cases, still encounter many limitations, including immunogenicity, high costs, and logistical problems concerning cell sourcing, in vitro expansion, and storage. Recent progress in 3D printing technologies offers a promising alternative: 3D‐printed cell‐free implants. By exploiting biomaterial‐driven activation and augmentation of the pro‐regenerative roles of endogenous stem/progenitor cells (ESPCs), via spatiotemporally controlled biophysical and biochemical cues, these medical devices can offer a scalable patient‐specific solution for cartilage or osteochondral regeneration. This perspective article argues that their success hinges on optimizing intricate scaffold design and fabrication to mimic native tissue hierarchy, elucidating ESPC recruitment and repair mechanisms, and addressing regulatory barriers to clinical translation. Fulfilling these criteria could democratize access to regenerative care while circumventing the ethical and practical pitfalls of exogenous cell‐ and in vitro‐expanded autologous cell‐based interventions.